2014
DOI: 10.1038/srep07366
|View full text |Cite
|
Sign up to set email alerts
|

How Unique was Hurricane Sandy? Sedimentary Reconstructions of Extreme Flooding from New York Harbor

Abstract: The magnitude of flooding in New York City by Hurricane Sandy is commonly believed to be extremely rare, with estimated return periods near or greater than 1000 years. However, the brevity of tide gauge records result in significant uncertainties when estimating the uniqueness of such an event. Here we compare resultant deposition by Hurricane Sandy to earlier storm-induced flood layers in order to extend records of flooding to the city beyond the instrumental dataset. Inversely modeled storm conditions from g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 37 publications
0
90
0
Order By: Relevance
“…Our model result for the storm tide, however, is only 2.66 m. One possible explanation for this is inaccurate wind speed estimates; a prior recent study using SLOSH found a higher wind speed is needed, relative to the Boose et al . [] study estimate of 51.4 m s −1 at landfall, to fit a presumed (inaccurate by +0.2 m) storm surge of 3.6 m, and the best fit came when maximum sustained wind speeds of 58 m s −1 [ Brandon et al ., ]. These results suggest that the Boose et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our model result for the storm tide, however, is only 2.66 m. One possible explanation for this is inaccurate wind speed estimates; a prior recent study using SLOSH found a higher wind speed is needed, relative to the Boose et al . [] study estimate of 51.4 m s −1 at landfall, to fit a presumed (inaccurate by +0.2 m) storm surge of 3.6 m, and the best fit came when maximum sustained wind speeds of 58 m s −1 [ Brandon et al ., ]. These results suggest that the Boose et al .…”
Section: Discussionmentioning
confidence: 99%
“…One widely cited [ Brandon et al ., ; Coch , ; Redfield , ; Scileppi and Donnelly , ] and impressive factor with the 1821 storm tide in NYH was that the water rose 13 feet in 1 h, based on a newspaper quote. The New Bedford Mercury quote read “In one hour during the [hurricane] of Monday evening, the water was forced into the East River 13 feet 4 inches [4.0 m] above low water mark.” [ Boose et al ., ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Sandy made landfall in southern New Jersey, it had maximum winds of only ∼70 knots (kts), but was a very large [tropical storm force winds extending about 870 nautical miles (4)] and slow-moving storm, capable of producing storm surge for an extended period in NYC (31). The hazard posed by storms of this type is amplified, because their long-duration storm surges have an increased likelihood of overlapping with a high astronomical tide to produce correspondingly larger flood heights.…”
Section: Resultsmentioning
confidence: 99%
“…Coastal geological archives have provided evidence of hurricane landfall (e.g., van de Plassche et al, 2006;Brandon et al, 2014), as well as European storm surges (e.g., Tsompanoglou et al, 2010;Bateman et al, 2018). However, use of the geological archive in geohazard assessment requires understanding of how such events are preserved in coastal environments.…”
Section: Introductionmentioning
confidence: 99%